2006
DOI: 10.1007/s00709-006-0177-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between induction of embryogenesis and chromosome doubling in microspore cultures

Abstract: The objective of this paper is to review the relationship between induction of microspore embryogenesis and chromosome doubling. It has been augmented with relative data on chromosome doubling by nuclear fusion. Some of the treatments used for induction of embryogenesis may also lead to doubling of the chromosome number, either through nuclear fusion or endomitosis. High frequencies of spontaneous chromosome doubling in cereal species appear to be induced by treatments that block cell wall formation during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Nuclear fusion has been proposed to be the main mechanism of spontaneous doubling in barley (González-Melendi et al 2005;Kasha et al 2001) and maize (Testillano et al 2004) microspore embryogenesis. High frequencies of spontaneous doubling in cereals appear to be induced by treatments that block cell wall formation during the first cell divisions (Shim et al 2006). Complete cytokinesis after n-butanol treatment or a likely role of cortical MTs in nuclear fusion could interfere with this process.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear fusion has been proposed to be the main mechanism of spontaneous doubling in barley (González-Melendi et al 2005;Kasha et al 2001) and maize (Testillano et al 2004) microspore embryogenesis. High frequencies of spontaneous doubling in cereals appear to be induced by treatments that block cell wall formation during the first cell divisions (Shim et al 2006). Complete cytokinesis after n-butanol treatment or a likely role of cortical MTs in nuclear fusion could interfere with this process.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the inductive effect of n-butanol on microspore embryogenesis is lower with a cold treatment than with mannitol. It is known that n-butanol disrupts cortical and interphase microtubules (Dhonukshe et al 2003, Gardiner et al 2003Hirase et al 2006) and that mannitol could also act as an antimicrotubule agent (Shim et al 2006). Our results indicated that mannitol and n-butanol could have an additive effect on microspore microtubule (MT) disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Sugar starvation by placing anthers on a medium with mannitol as the carbohydrate source is one of the most commonly used stress pre-treatments (Caredda et al, 2000;Kasha et al, 2001; Cistué et Soriano et al, 2007;Castillo et al, 2015). This pre-treatment has resulted in consistently high chromosome doubling rates in barley (Kasha et al, 2001;Shim et al, 2006) and wheat (Hu and Kasha, 1997). In addition, Cistué et al (2006) reported that pre-treating the anthers in 0.7 M mannitol for five days improved green plant regeneration in durum wheat.…”
Section: Discussionmentioning
confidence: 99%